Keanekaragaman Pteridophyta di Tahura Nuraksa Kabupaten Lombok Barat - Ningsih, Widia Ayu; Hadiprayitno, Gito; Handayani, Baiq Sri (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Pteridophyta is a pioneer plant that has an important role because it can provide benefits for human life and the environment. Pteridophyta can maintain the balance of the forest ecosystem, namely regulating water levels, helping the weathering process of forest litter, and as a soil cover in the forest, thereby preventing erosion. The distribution of Pteridophyta plant populations is influenced by several factors including humidity, light, and sufficient water sources. This study uses a descriptive exploratory method which aims to determine the types of Pteridophyta and obtain the diversity index value of Pteridophyta species in Tahura (Taman Hutan Raya) Nuraksa, West Lombok Regency. Pteridophyta sampling used the quadratic method by making plot arranged in a zigzag with a size 5m x 5m. The results showed that the number of Pteridophyta found was 18 species, 12 genera, and 8 families (Athyriaceae, Denstaedtiaceae, Dryopteridaceae, Lomariopsis, Polypodiaceae, Pteridaceae, Tectariaceae, and Thelyptheridaceae. Analysis of Pteridophyta species diversity index using the Shannon-Wiener formula and obtained a species diversity index value (H') for all species of 2.209, with a medium species diversity category. The value of this diversity index shows the amount of variation in species and growth of Pteridophyta in accordance with environmental conditions in Tahura Nuraksa.